The British hotel through the ages - Borer, Mary Cathcart, 1906-1994 (Lutterworth Press, 2021)
The first inns in Britain were built by the Romans, for the accommodation of road builders and government officials. Their history since then ranges from pilgrim hostels built by monasteries to coaching inns and palatial railway hotels. Throughout this book runs a rich vein of social history detailing the food, drink, furnishings and costs of British hotels. Travellers' tales, both British and foreign, from the sixteenth century onwards, are quoted at length, so that the book comes alive with first-hand impressions. We learn how some of the Regency Hotels of London came into being, such as Grillion's, where Louis XVIII stayed in 1814, and there are accounts of the early railway hotels, and the great provincial hotels of Britain's coast and countryside. Mary Cathcart Borer's study still provides a detailed historical perspective of her subject almost fifty years on from its first publication, while at the same time offering a glimpse of contemporary attitudes to the rapidly expanding British hotel trade in the 1970s.